Role of transient receptor potential vanilloid 1 in the modulation of airway smooth muscle tone and calcium handling - Yocum, Gene T. (Am J Physiol Lung Cell Mol Physiol, 2017)
Asthma is a common disorder characterized, in part, by airway smooth muscle (ASM) hyperresponsiveness. Transient receptor potential vanilloid 1 (TRPV1) is a nonselective cation channel expressed on airway nerve fibers that modulates afferent signals, resulting in cough, and potentially bronchoconstriction. In the present study, the TRPV1 transcript was detected by RT-PCR in primary cultured human ASM cells, and the TRPV1 protein was detected in ASM of human trachea by immunohistochemistry. Proximity ligation assays suggest that TRPV1 is expressed in the sarcoplasmic reticulum membrane of human ASM cells in close association with sarco/endoplasmic reticulum Ca(2+)-ATPase-2. In guinea pig tracheal ring organ bath experiments, the TRPV1 agonist capsaicin led to ASM contraction, but this contraction was significantly attenuated by the sodium channel inhibitor bupivacaine (n = 4, P < 0.05) and the neurokinin-2 receptor antagonist GR-159897 (n = 4, P < 0.05), suggesting that this contraction is neutrally mediated. However, pretreatment of guinea pig and human ASM in organ bath experiments with the TRPV1 antagonist capsazepine inhibited the maintenance phase of an acetylcholine-induced contraction (n = 4, P < 0.01 for both species). Similarly, capsazepine inhibited methacholine-induced contraction of peripheral airways in mouse precision-cut lung slice (PCLS) experiments (n = 4–5, P < 0.05). Although capsazepine did not inhibit store-operated calcium entry in mouse ASM cells in PCLS (n = 4–7, P = nonsignificant), it did inhibit calcium oscillations (n = 3, P < 0.001). These studies suggest that TRPV1 is expressed on ASM, including the SR, but that ASM TRPV1 activation does not play a significant role in initiation of ASM contraction. However, capsazepine does inhibit maintenance of contraction, likely by inhibiting calcium oscillations.